Intensitas Serangan Jamur Ganoderma sp Pada Tanaman Kelapa Sawit Rakyat Asal Bibit Unggul Dan Bibit Non Unggul - Hayata Hayata; Rudi Hartawan; Reza Andre Saputra (Jurnal Media Pertanian, 2026)
Oil palm is a strategic plantation commodity that plays a vital role in Indonesia’s economy as a major contributor to non-oil and gas revenue. Its high productivity and market value make it an attractive investment. However, basal stem rot (BSR) caused by Ganoderma sp. remains a major constraint in plantation management. This study aims to compare the incidence and severity of the disease between oil palms derived from improved and non-improved seeds. The research was conducted from August to November 2024 in Suban Village, Batang Asam District, Tanjung Jabung Barat Regency using an unformatted trial design with purposive site selection. Data were collected through field symptom observations, farmer interviews, and environmental factor measurements, then analyzed qualitatively (data tabulation) and quantitatively (paired t-test). The results revealed that palms from improved seeds showed a disease incidence of 2.96% with 2.14% severity, while non-improved seeds exhibited 3.33% incidence with 1.85% severity. These findings indicate that improved seeds are relatively more resistant to Ganoderma sp. infection, although the disease severity tends to be slightly higher. This study provides important insights for disease management strategies and serves as a reference for farmers in selecting seed sources to optimize oil palm productivity.